2012
DOI: 10.3389/fnhum.2012.00270
|View full text |Cite
|
Sign up to set email alerts
|

Altered negative priming in older subjects: first evidence from behavioral and neural level

Abstract: The impact of aging on the negative priming (NP) effect has been subject of many studies using behavioral measures. Results are inconsistent and corresponding neural data do not exist. We were interested in, whether or not processing of NP is altered in older in comparison to young adults (YA) on behavioral and neural level. Eighteen young and eighteen older healthy adults performed a location-based NP paradigm during fMRI. YA behaviorally showed a NP effect and NP associated fronto-striatal activation, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…Also, findings from ERPs and fMRI support our suggestions that the fronto-parietal network is involved in spatial priming during visual attention tasks and that an inhibitory top-down process is responsible for negative priming effects at prior distractor positions instead of delayed episodic retrieval (e.g. Bauer et al, 2012;Gibbons, 2006;Kathmann et al, 2006;Kehrer et al, 2009;Krueger et al, 2007;Ruge and Naumann, 2006;Wright et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Also, findings from ERPs and fMRI support our suggestions that the fronto-parietal network is involved in spatial priming during visual attention tasks and that an inhibitory top-down process is responsible for negative priming effects at prior distractor positions instead of delayed episodic retrieval (e.g. Bauer et al, 2012;Gibbons, 2006;Kathmann et al, 2006;Kehrer et al, 2009;Krueger et al, 2007;Ruge and Naumann, 2006;Wright et al, 2006).…”
Section: Discussionsupporting
confidence: 70%
“…Bauer et al, 2012;Kathmann et al, 2006;Krueger et al, 2007;Ruge and Naumann, 2006;Wright et al, 2006). It has been shown that the size of negative and positive priming effects can vary with task demands (e.g.…”
Section: Limitations Of the Study And Perspectivesmentioning
confidence: 97%
“…It is generally accepted that normal aging can lead to declines in cognitive performance (Braver and Barch, 2002;Craik and Salthouse, 2011;Andrews-Hannah et al, 2007;Geerligs et al, 2014a;2014b;Grady, 2012;Larson et al, 2016;Li et al, 2001;2016;Persson et al, 2006;Zanto et al, 2010). More specifically, there is a plethora of evidence highlighting impairments in inhibition mechanisms (Hasher and Zacks, 1988;Bauer et al, 2012;Mayas et al, 2012;Gazzaley et al, 2005; but see Frings et al, 2015 for contrasting findings). Previous studies have highlighted the increased interference experienced from irrelevant distractors in old age across different experimental paradigms such as global/local tasks (Tsvetanov et al, 2013;Mevorach et al, 2016), reading with distractor tasks (Darowski et al, 2008), response inhibition (Anguera and Gazzaley, 2012), as well as inhibition in the context of WM tasks (Gazzaley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Priming is an implicit memory effect where prior exposure to a stimulus influences responses to the next stimulus. Negative priming tasks have previously been shown to engage inferior frontal and striatal (caudate nucleus) networks (Bauer et al, 2012). In this task (based on Bauer et al, 2012), participants are presented with displays containing an ‘X’ and an ‘O’, which can appear in two of four possible locations, and are required to indicate the position of the ‘X’ while ignoring the ‘O’.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, DA-dependent (fronto)-striatal circuits have been shown to play a pivotal role in implicit measures, in healthy controls (e.g. Bauer et al, 2012), as well as in patient studies (e.g. Foerde and Shohamy, 2011; van Asselen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%